2008
DOI: 10.1080/00016340802014748
|View full text |Cite
|
Sign up to set email alerts
|

Complete destruction of urethra and bladder neck following symphysiotomy and results of attempted corrective surgery

Abstract: Four (0.8%) out of 526 obstetric fistulas were related to a preceding symphysiotomy procedure. Complete destruction of the urethra and bladder neck with retropubic fibrosis was found. Faulty technique is the most probable cause. All women had stillborn babies before the symphysiotomy delivery, and tissue damage due to obstructed labor could have been a predisposing factor. A neo-urethra was successfully constructed in three of the four women, but continence in standing position was not obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…In addition, some fistulae were probably iatrogenic owing to malperformed vaginal interventions (Table 1). Symphysiotomy-related fistulae [11] and sexual violence-related fistulae [12] have also been reported from the same clinic.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, some fistulae were probably iatrogenic owing to malperformed vaginal interventions (Table 1). Symphysiotomy-related fistulae [11] and sexual violence-related fistulae [12] have also been reported from the same clinic.…”
Section: Discussionmentioning
confidence: 83%
“…Information was obtained from standardized registration forms, patient cards, and surgery records and included data on patient demographics, obstetric history, clinical data related to the index pregnancy, surgical information, fistula characteristics, and fistula etiology as considered by the surgeon. Only patients whose records included information on the etiology and localization of the fistula International Journal of Gynecology and Obstetrics 114 (2011) [10][11][12][13][14] were included in the present study. The study was approved by the Regional Committee for Medical Research Ethics of Southern Norway and by the Director of Panzi Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Complete destruction of the urethra has been described earlier (6) as a complication of failed UF repairs, traditional practices like ‘yankan gishiri’ and even measles, but perhaps as the authors claim (1), lack of ST training should be added. One of us (TJIPR) has operated more than 4,000 UFs.…”
mentioning
confidence: 90%
“…Onsrud et al (1) do not inform us about the CS and craniotomy rate of the other 522 women with UF. In a thesis describing in detail 500 patients with UF (6), 95.8% associated with perinatal mortality, it was found that in at least 5.6% of the cases, the fistula was caused by a CS because there was a vesico‐cervicovaginal fistula with (partial) loss of the anterior cervix.…”
mentioning
confidence: 95%
See 1 more Smart Citation